2021
DOI: 10.1111/ppe.12767
|View full text |Cite
|
Sign up to set email alerts
|

Breast feeding and timing of puberty in boys and girls: A nationwide cohort study

Abstract: Background Breast feeding has been associated with improved infant health, but its impact on pubertal timing remains uncertain, particularly in boys. Objective The objective of this study was to investigate the association between duration of breast feeding and pubertal timing in boys and girls. Methods This population‐based cohort study included 13 511 boys and girls from the Puberty Cohort nested within the Danish National Birth Cohort. The children gave half‐yearly, self‐reported information on pubertal dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Briefly, 22 articles investigated the association between childhood diet or nutrients and early puberty. In addition, six articles [ 16 , 21 , 22 , 23 , 24 , 25 ] provided the effects of breastfeeding duration in infancy on the timing of menarche and breast development. Among the included studies, five were cross-sectional one was a case-control study [ 26 ], and 22 were cohort studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, 22 articles investigated the association between childhood diet or nutrients and early puberty. In addition, six articles [ 16 , 21 , 22 , 23 , 24 , 25 ] provided the effects of breastfeeding duration in infancy on the timing of menarche and breast development. Among the included studies, five were cross-sectional one was a case-control study [ 26 ], and 22 were cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“… Forest plot of the association between breastfeeding duration in infancy and early menarche onset [ 21 , 22 , 23 , 24 ]. …”
Section: Figurementioning
confidence: 99%
“…In a recent population-based cohort study in 13,511 boys and girls, a shorter duration of breastfeeding was associated with earlier pubertal development in boys but not in girls. Specifically, boys who were never breast-fed attained pubertal markers earlier (~4.1 months) than boys exclusively breastfed for at least four months [129]. In girls, the duration of breastfeeding was not associated with pubertal development [129].…”
Section: Breastfeedingmentioning
confidence: 89%
“…Specifically, boys who were never breast-fed attained pubertal markers earlier (~4.1 months) than boys exclusively breastfed for at least four months [129]. In girls, the duration of breastfeeding was not associated with pubertal development [129].…”
Section: Breastfeedingmentioning
confidence: 89%
“…Genetic factors are major determinants of age at menarche but other environmental factors such as exposures to endocrine‐disrupting chemicals (Buttke et al, 2012), decline of breastfeeding (Hvidt et al, 2021), specific dietary intake (Ramezani Tehrani et al, 2013; Wiley, 2011) and childhood overweight/obesity (Al‐Awadhi et al, 2013) have been suggested to play a significant role in the decline of age at menarche. Vitamin D may contribute to the timing of menarche through musculoskeletal development as body size measures have been associated with early menarche (Freedman et al, 2002; Lindgren, 1978; Morrison et al, 1994).…”
Section: Introductionmentioning
confidence: 99%